Stakeholder perspectives to improve risk management in European farming systems - Daniele Bertolozzi-Caredio; Isabel Bardají; Alberto Garrido; Robert Berry; Jo Bijttebier; Camelia Gavrilescu; Hristina Harizanova; Błażej Jendrzejewski; Miranda M.P. Meuwissen; Franziska Ollendorf; Corentin Pinsard; Jens Rommel; et al. (Journal of Rural Studies, 2021)
The challenges faced by agricultural systems call for an advance in risk management (RM) assessments. This research identifies and discusses potential improvements to RM across 11 European Union (EU) farming systems (FS). The paper proposes a comprehensive, participatory approach that accounts for multi-stakeholder perspectives relying on 11 focus groups for brainstorming and gathering suggestions to improve RM. Data analysis is based on content analysis and coding of suggested improvements, and their assessment through the lenses of main challenges faced, farms' flexibility, and dependence on subsidies. First, the results show that necessary improvements differ depending on whether they have their origin in sudden shocks or long-term pressures. Second, farm dependence on direct payments determines a stronger need to improve financial instruments, whereas farm flexibility suggests a need for more accessible and tailored tools for low-flexibility FS, and increased know-what and know-how for high-flexibility FS. Third, our findings indicate a potential for extending stakeholder involvement in RM to new or unconventional roles. Underlying specific improvements, the paper suggests and discusses three main avenues to improve RM as a whole: i) a developed learning and knowledge network; ii) new forms of collaboration; and iii) integrated financial and policy instruments.
Keywords: 630; focus group; participatory assessments; European farming systems; agricultural insurance; cooperation; knowledge systems